Risk factors of ovarian cancer among women at selected hospitals in the Klang Valley, Malaysia - John, Ugwu Osmong (2019)
Ovarian cancer is otherwise called the silent killer because it is asymptomatic in the early stages and this leads to late diagnosis in most cases. Despite being a disease with rare incidence in most parts of the world, it is globally the most common cause of gynaecologic cancer deaths. In Malaysia, about 56% cases of ovarian cancer were diagnosed in their late stages. Ovarian cancer incidence has witnessed period increase among Malaysian women from 543 in years 2005 to 714 in year 2011 (an increase of 31.5% within six years). The exact aetiology of ovarian cancer is not yet fully understood and there is limited published studies to show the factors associated with this disease in Malaysia. The objective of this study was to identify the risk factors of ovarian cancer among Malaysian women. This hospital-based case-control study was conducted in three government hospitals in Klang Kalley from March 2017 to November 2018. The studied subjects included 111 histopathological confirmed cases of ovarian cancer diagnosed within 3 years to the time of recruitment and 134 controls. Self-administered questionnaire was used to obtain information on subjects’ sociodemographic characteristics, medical history, family history of cancer, reproductive history, and smoking habit. Multiple logistic regression analysis was conducted and adjusted odds ratio (AOR) and p-value were used to determine the significant risk factors. Results showed that the odds of first pregnancy after the age of 25 years among cases was more than two times higher than in the controls (AOR=2.360, 95%CI: 1.105, 5.040; p=0.027). In addition, the odds of first-degree family member having history of cancer among cases was almost 3 times higher than in the controls (AOR=2.994, 95%CI: 1.088, 8.245, p=0.034) after adjusting for age and ethnicity. In conclusion, delay in first pregnancy and having family member with history of cancer are important risk factors. These high-risk groups should be considered for primary and secondary prevention of ovarian cancer.